The role of expectation management in value creation: A case study on municipal managers' experiences with offering supported housing - Kim Ulvin; Laila Tingvold; Karina Aase; Siv Fladsrud Magnussen (Administrative Sciences, 2024)
Theoretically rooted in public service logic (PSL), this article explores managers' experiences constructing value propositions and facilitating the value creation process in a public sector environment. It reports on a qualitative study from a Norwegian municipal setting based on individual and focus group interviews supported by participant observations and relevant documents. The data were analyzed according to the guidelines of stepwise-deductive inductive analysis (SDI). The findings substantiate changes in the utilized supported housing forms and highlight urgency's pervasive effect on transition processes to supported housing for individuals with intellectual disabilities and the need for around-the-clock support. This study contributes to public management research by examining the process of constructing value propositions and the managers' efforts to contribute to the formation of more realistic expectations towards the municipality's scope and level of service among prospective service users and their families. The article contributes to the PSL discourse by providing the complementary concept of expectation-reality mitigation as a particular form of expectation management suited for the complexities and constraints of value creation in public service settings.
Keywords: 350; public service logic; co-creation; case study; social services; vulnerable service users